PENGARUH PENDIDIKAN KARAKTER TERHADAP PRESTASI BELAJAR SISWA DI SMP N 3 BOJA - Mudzalifah; Noor Miyono (STKIP Subang, 2023)
This research aims to see the effect of character education on student learning achievement in class VII at SMP Negeri 3 Boja. With a class VII population of 102 students and the sample in this study was taken 25% of the total population of 26 people. This research is quantitative research using simple linear regression analysis techniques. The results obtained in this research are that there is an influence of character education on student learning achievement. This can be seen from the influence of character education which influences learning achievement by contributing 25%. This means that 75% of student learning achievement is influenced by other factors not examined in this research. Based on the description above, it can be concluded that character education influences student achievement results at SMP N 3 Boja, Boja District, Kendal Regency. This shows that the better character education is applied to students, the better the students' learning achievement at the school.